Diagnóstico coproparasitológico e detecção de anticorpos anti-Strongyloides stercoralis em amostras de soros de cães domésticos - Ferreira Júnior, Álvaro (2005)
Canine strongyloidiasis is a parasitic infection caused by the nematode Strongyloides stercoralis and presents a great zoonotic potential.As its confirmation by using coproparasitologicai methods is not easy, the detection of serum specific antibodies could contríbute to the diagnosis. The aim of thís study was to investigate the presence of S. stercoralis by parasitological methods and to detect specific antibodies to the parasite in serum samples from domestic dogs by using the indirect fluorescent antibody test (IFAT) in slides and enzyme-linked immunosorbent assay (ELISA). A total of 215 dogs of various breeds, coming from Uberlândia, Araxá and Campo Belo, State of Minas Gerais, were studied and distributed according to age in the following groups. (I) 19 male and 20 female dogs, with 1 to 2 months old; (II) 11 male and 20 female dogs, from 2 months to 1 year old;(III) 41 male and 104 female dogs, from 1 to 7 years old. Coproparasitological resuits showed that 63/215 (29.3%) dogs presented some kind ofparasite, with 2 (0.9%) dogs (one from Araxá and another from Uberlândia) exhibiting S. stercoralis larvae in feces. Serological resuits revealed antibodies to S. stercoralis in 45/215 (20.9%) dogs, with seropositivity rates of 0% (0/39) in group I, 22.6% (7/31) in group II. and 26.2% (38/145) in group III. No serological cross-reactivity between S. stercoralis and hookwomis or Ascaridae was found. Only one dog with biparasitism (hookworm and Cysloisospora spp) was also S. stercoralis seropositive in IFAT. The present study demonstrated for the first time the natural S. stercoralis infection in dogs that was diagnosed by coproparasitologicai and serological methods. Also, the detection of specific antibodies to S. stercoralis by IFAT and ELISA could contribute to the diagnosis ofcanine strongyloidiasis.